Growth and Initial Development of Pitaya White (Hylocereus undatus) and Red (Hylocereus monacanthus) in the City of Araguaína-TO (Research, Society and Development, 2021)
The pitaya is a tropical fruit belonging to the Cactaceae family and originating from Central and South America, which has attracted researchers and producers for its flavor and color. It is an exotic fruit and has become a source of income for family farming as its fruits have a high market value and demand is growing. The experiment was installed in the experimental area of the Centro Universitário Tocantinense Presidente Antônio Carlos (UNITPAC) in the municipality of Araguaína, Tocantins. The objective of the work was to evaluate the initial growth and development of the red and white pitaya in the city of Araguaína - TO. The design used was in randomized blocks and the treatments consisted of two cultivars, with five replications. Clones of the red and white pitaya cultivars were used to form the orchard, with a spacing of 2.5 x 1.5 m. The variables evaluated were: height, stem diameter and number of cladodes. In relation to the diameter of the stem, both cultivars presented a similar performance, however. Regarding the average number of cladodes per plant, both species presented similar amount of cladode emissions, obtaining an average of 15 cladodes per plant. The white pitaya had an average height of 1.91 m, while the red pitaya had an average height of 1.93 m after 11 months of implantation. Both clones show good growth and initial development under the edaphoclimatic conditions of Araguaína-TO.